Superconductivity in Group III-V Semiconductor AlN Under High Pressure - Dancy, G. Selva; Sheeba, V. Benaline; Louis, C. Nirmala; Amalraj, A. (Orbital: The Electronic Journal of Chemistry, 2013)
The electronic properties of cubic zinc blende type group III-V semiconductor AlN under pressure is studied using full potential linear muffin-tin orbital (FP-LMTO) method. At normal pressure, AlN is an indirect bandgap semiconductor with band gap value 4.56 eV. When the pressure is increased, there is enhanced overlapping between the wave functions of the neighboring atoms. As a result the widths of the valence and empty conduction bands increase. These changes lead to the narrowing and indirect closing of the band gaps in AlN (metallization). On further increase of pressure, AlN becomes a superconductor and AlN comes under the class of electron-phonon-mediated high pressure superconductors. The superconducting transition temperatures (Tc) of AlN are obtained as a function of pressure for the CsCl structure. It is also confirmed that the metallization, structural phase transition and onset of superconductivity do not occur simultaneously in this compound.DOI: http://dx.doi.org/10.17807/orbital.v7i3.628